2013
DOI: 10.1002/per.1853
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Identity Dimensions with Big Five Personality Domains and Facets

Abstract: Personality is among the most important factors contributing to individual differences in identity formation. However, previous studies mainly focused on broad personality domains and neglected more specific facets. In addition, it has only recently been recognized that identity formation is guided by multiple types of commitment and exploration. The present study aimed to remedy these limitations by relating the 30 personality facets of the NEO‐PI‐3 to five identity dimensions. In general, identity formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 37 publications
6
56
2
1
Order By: Relevance
“…To clarify the adaptive development of regional identity, we investigated meaningful associations with personality traits and life satisfaction. In line with previous research (Crocetti et al, ; Klimstra et al, ), we hypothesized that a more established regional identity status goes along with personality traits associated with maturity and higher life satisfaction.…”
Section: The Present Studysupporting
confidence: 63%
“…To clarify the adaptive development of regional identity, we investigated meaningful associations with personality traits and life satisfaction. In line with previous research (Crocetti et al, ; Klimstra et al, ), we hypothesized that a more established regional identity status goes along with personality traits associated with maturity and higher life satisfaction.…”
Section: The Present Studysupporting
confidence: 63%
“…Furthermore, Klimstra, Luyckx, Hale, and Goossens (2014) focused on longitudinal predictors of externalizing behavior and found that associations within certain domains were facet-specific (e.g., the reported association between extraversion and alcohol abuse was mainly due to the facets of sociability and activity). In another study, Klimstra, Luyckx, Goossens, Teppers, and De Fruyt (2013) found that associations between negative emotionality and ruminative exploration of identity were mainly due to internalizing facets of negative emotionality (e.g., anxiety, depression, etc.). Mund and Neyer (2014) also reported facet-specific effects, such as the finding that the conscientiousness facet of dependability (but not the total conscientiousness domain score) predicted decreases in insecurity in relationships with kin, and the extraversion facet of activity (but not the total extraversion domain score) predicted increases in closeness in relationships with kin.…”
Section: Predictive Validity and Demographic Correlates Of Big Five Fmentioning
confidence: 96%
“…The links between the sense of identity and higher-order personality factors such as the Big Five are well-established (Klimstra, Luyckx, Goossens, Teppers, & De Fruyt, 2013;Lounsbury, Levy, Leong, & Gibson, 2007). However, there still is a need to study the role of more narrow and specific lowerorder personality characteristics (McAdams & Pals, 2006).…”
Section: The Three-dimensional Conceptualization Of Parental Identitymentioning
confidence: 99%